Playing with fire: the civil liberties implications of September 11th - Gould, Jon B. (2002)
The aftermath of September 11th has seen a worrisome rise in invasive surveillance measures. Both adopted by statute and initiated by agencies, these provisions provide unprecedented powers for government agents to investigatge suspects and search individuals, whether they are directly involved in terrorism or not. The prevailing wisdom has been that the American people will accept these restrictions as the natural cost of heightened security, and initial evidence suggests the public has been willing to tolerate greater limits on civil liberties. However, over time such support will erode, leaving in place permanent restrictions on civil liberties that not only will concern Americans, but also may turn them against government officials and civic participation. Thus, contrary to many interpretations of September 11th, this article argues that the policy response has only sown the seeds for greater detachment from and dissatisfaction with government as the public becomes increasingly separated from the workings and operations of public policy. - Reproduced.
Keywords: Human rights - United States; Human rights